VD_FINDINFO Arrêt / 2011 / 879 vom 27. Mai 2011 - VD Tribunal cantonal (2011)
RECOURANT, TUTELLE, À TITRE VOLONTAIRE, MALADIE MENTALE, OPPOSITIONPROCÉDURE | 369 CC, 372 CC, 388 al. 3 CC, 379 CPC, 393 CPC, 174 al. 2 CDPJ